Voltammetric determination of imidacloprid and thiamethoxam - SZILVIA N. ÖKRÉSZ; LUKA J. BJELICA; FERENC F. GAÁL; VALÉRIA J. GUZSVÁNY (Journal of the Serbian Chemical Society, 2005)
A simple voltammetric method using a glassy carbon working electrode was developed for the determination of two members from the neonicotinoid group of insecticides: imidacloprid and thiamethoxam. The experiments showed that the voltammetric response depends on the mode of electrode surface pretreatment and the polarization mode. The response appeared to be linear in the range from 0.028 to 0.50 mg/cm3 for both analytes. The limit of detection was 0.0077 mg/cm3 for imidacloprid and 0.0085 mg/cm3 for thiamethoxam, the limit of quantitation was 0.026 mg/cm3 and 0.028 mg/cm3, respectively. The developed method was applied for the determination of these insecticides in potato samples sprayed with Confidor 200-SL or Actara 25-WG as well as commercial formulations of imidacloprid and thiamethoxam. Arecovery trial was performed to assess the accuracy of the results, the recovery values being between 95–102 % for both of neonicotinoids.